The effects of stress inoculation training on coping strategies among midwives in primary health-care centers - Maryam Navaee; Hadis Kaykha (Kashan University of Medical Sciences, 2019)
Background: Effective coping with stress is the main component of interpersonal communication. It helps people overcome their conflicts and problems in their interpersonal and social relations. Objectives: This study sought to examine the effects of stress inoculation training (SIT) on coping strategies among midwives in primary health-care centers. Methods: In this two-group, quasi-experimental study, eighty midwives were randomly selected from health-care centers in Zahedan, Iran, and were randomly allocated to an intervention and a control group. The study intervention was an SIT program offered in two 4-h workshops weekly held in 2 consecutive weeks. Participants in both groups responded to the Coping Responses Inventory (CRI) before, immediately after, and 1 month after the intervention. Data were analyzed using the independent-sample t and the Chi-square tests as well as the repeated-measures analysis of variance. Results: The mean score of coping strategies statistically significantly increased in the intervention group from 36.20 ± 7.50 at pretest to 47.22 ± 9.97 1 month after the intervention (P < 0.001). One month after the intervention, there were significant between-group differences in the CRI respecting the mean scores of coping strategies and all its subscales (P < 0.05), except for the problem-focused coping subscale (P = 0.06). Conclusion: SIT can be used to improve midwives' coping with stress.